Levels and criteria for understanding of the scientific text in the pre-university period - Kharitonova, Olga (2021)
The article covers the issues concerning the levels and criteria of preparatory department students' understanding of the scientific text. Teaching scientific language presupposes work with scientific texts at a language proficiency level of A1. When teaching how to work with the scientific text, one should consider its pragmatic, contents and cognitive discourse functions. Understanding is a multi-level psychological category, which determines foreign students' way of reading the scientific text. Each of the levels forms certain skills of text understanding. The article proves that comprehension of the depths of meaning is one of the criteria of scientific text understanding.